HOSPITALâS ROLE IN IMPLEMENTING 30-BAHT PROGRAM FOR HEALTH SECURITY IN CHONBURI PROVINCE, THAILAND - Wilujeng, Nievia Afina (FIA UB, 2013)
Abstract: Hospitalâs Role In Implementing 30-Baht Program For Health Security In Chonburi Province, Thailand. The 30-Baht-program in Thailand has a good trend at the first stage to cover healthcare for Thai people in reaching health security, but currently it faces difficulties of service delivery in lower level: hospital. This is a qualitative approach study to investigate the obstacles in Chonburi Province. A series of interview with selected informants and observation to two hospitals describes the policy implementation, confirms the role of hospital, and the publicâs perspective about the issue. The data shows that hospital deals the complicated administration, high tendency for visiting hospital for minor sickness since it is low cost, and many patients agree of improving healthcare service. It is recommended to Thai Government to simplify the administration work, to reexamine budget necessity, and to listen to the public in evaluating the policy. Key words: policy implementation, health security, 30-Baht-program, Thailand Â Abstrak: Peran Rumah Sakit Dalam Menerapkan 30 Baht Program Untuk Keamanan Kesehatan Dalam Chonburi Province, Thailand. Kebijakan 30-Baht di Thailand menunjukkan perkembangan yang baik pada awal penerapannya untuk menyediakan layanan kesehatan bagi masyarakat Thailand sehingga mewujudkan health security. Namun keadaan terkini memperlihatkan bahwa ada beberapa hambatan dalam pemberian layanan kesehatan, terutama pada level terbawah, yaitu rumah sakit. Ini adalah studi dengan pendekatan kualitatif untuk meneliti implementasi kebijakan 30-Baht tersebut di Chonburi Province. Serangkain wawancara kepada informan tertentu dan observasi pada dua rumah sakit terpilih telah dilakukan untuk mendapatkan gambaran implementasi kebijakan ini, mengetahui peran rumah sakit, dan mendapatkan sudut pandang publik terhadap masalah terkait. Data menunjukkan bahwa rumah sakit menghadapi kesulitan dalam hal administrasi, ada kecenderungan yang tinggi untuk berobat hanya untuk sakit ringan, namun juga banyak yang setuju adanya peningkatan layanan kesehatan. Kata kunci: implementasi kebijakan, health security, program 30-Baht, Thailand